Reward And Punishment In Islamic Education - Mustofa, Ali; Istikomah, Rohmah; Ma’mun, Muhammad Aman (Postgraduate Program Magister Pendidikan Agama Islam, 2019)
ABSTRACT: Nowdays, there are a lot of many things in the societythat leads to pro and contra issues. For example, violence in the education. This is agains to child protection laws in Indonesia. In the Islamic education, hitting a child is allowed. It based on hadith of our Prophet Muhammad SAW. Of course, this action has to follow the rule and it has educational purpose. This study aims to know how reward and punishment applied based on the Islamic educational’s point of view. Another aims is toknow the relevation of reward and punishment in education mistake is allowed but it has to pay attention to the way how to hit the child in the appropriate way. A child is allowed to be hitting only with a light hit and it aims to give him/her a reminder about his/her mistake. This action agains to the child protection laws in Indonesia since no violence in education. In other hand, a teacher has a right and an obligation to be obeyed. In the laws, it mentioned that a teacher has a right to give the student sanctions only in the one condition: it based on code of educators’ ethics.